Measuring local government performance in Malaysia: political indicators versus organisational theory / Zaherawati Zakaria - Zakaria, Zaherawati (Universiti Teknologi MARA, Kedah, 2011)
There are localities in Malaysia where local government performance is systematically superior and others where it is inferior. Similar institutions perform that systematically perform better than others always raise queries and objection among people. Recognizing the enormous practical implications of this question for local democratic governance in Malaysia, this paper looks at the decision-makers and researchers to assess and explain local government performance. Thus, this paper looks at the concept of local government performance and uses a wide variety of variables to gauge its variance on the one hand, and its roots in economic, political, legal, cultural and social factors on the other.